Buteelch-5, A Traditional Formula Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice - Hasiqiqige; Zhang, Fanfan; Dalkh, Tserendagva; Sharav, Bold; Perenlei, Molor-Erdene (Central Asian Journal of Medical Sciences, 2019)
Objectives: To examine the therapeutic effects of buteelch-5, a traditional formula on DSS-induced colitis in C57/BL6 mice and its possible mechanisms. Methods: Colitis in mice was induced by oral administration of 5% dextran sulfate sodium (DSS) for seven days. On the eighth day after administration of DSS, buteelch-5 (500 mg/kg, twice a day) was given orally to mice for five consecutive days. Ciprofioxacin (50 mg/kg, once a day for 5 days) was given to mice as a comparison. Two hours after the last administration of buteelch-5 and ciprofioxacin, mice were euthanized, and colon tissues were removed. Protein and mRNA levels of occludin, claudin-1 and zonula occludens (ZO)-1 in colon tissues were determined by western blot and real time-qPCR respectively. Histopathological analysis of colon tissues was performed. Results: Histological analysis revealed successful establishments of colitis models. Treatment with buteelch-5 markedly inhibited DSS-induced colon injury. Furthermore, buteelch-5 increased (2.14-2.67 fold) the occludin, claudin and ZO-1 protein and mRNA levels in colon tissues of mice administered with DSS. Significant increase was observed in occludin mRNA levels after buteelch-5 treatment (p<.05). Conclusion: Buteelch-5 improves microscopic inflammation and increases tight junction protein expressions such as occludin, claudin, and ZO-1 in mice with DSS-induced colitis.